The value of emotional intelligence for high performance coaching - A commentary - Crombie, D. (International Journal of Sports Science and Coaching, 2011)
While appreciating the authors` endeavour to demonstrate the value of EI for coaches/coaching performance, the author argued that problematic issues related to EI leadership literature compromise its appropriateness for their purpose and reliance upon it undermines their efforts. That EI and coach/coaching performance is a most worthy research focus in not in question. However, in pursuing the quest for compelling empirical evidence researchers undertaking such studies must safeguard against ontological and epistemological decisions that may not be appropriate.